Pendekatan Perencanaan Strategis Untuk Administrasi Perpajakan Di Rumah Sakit (Studi Kasus RSU Bhakti Yudha Depok Jawa Barat) - Rahman, Abdul (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2009)
Hospital represent one of effort institution which active in service of health. Hospital represent Income Tax (PPh) subject if delivering Goods which is PPN Object than Rp. 600.000.000,-. RSU Bhakti Yudha Depok represent hospital which located in town region of Depok representing region of Dati II. As Subjek of TAX, rsu Bhakti Yudha Depok do obligation of its taxation, among others PPh, PPN and PPh Secction 21 to all itts employees.